The SAMD1 transcription factor coordinates hematopoietic lineage differentiation and H3K4 methylation status - Meg A. Schaefer; Samantha L. Gomez; Venkatasai Rahul Dogiparthi; Yichao Zhou; Pooja Roy; Suhita Ray; Linda Chee; Sandipan Brahma; Robert Liefke; Kyle J. Hewitt (Blood Advances)
Abstract: Cell progenitor to progeny transitions depend on precise transcriptional mechanisms to adjust gene expression. The sterile α-motif–containing 1 protein (SAMD1) regulates a shift in transcriptional activity during embryonic stem cell exit from pluripotency. SAMD1 interacts with, and facilitates the activity of, the histone H3 lysine-specific demethylase 1 (LSD1; a lysine demethylating enzyme). SAMD1 is expressed throughout many biological systems, but its role in hematopoiesis is unknown. In human and mouse hematopoietic stem/progenitor cells, we tested the role of SAMD1 in hematopoiesis and erythropoiesis using loss-of-function approaches. SAMD1 promoted expression of critical drivers of hematopoiesis, including the GATA binding protein 2 transcription factor, while opposing erythroid programs. Loss of SAMD1 in ex vivo differentiating cells increased erythroid and megakaryocyte differentiation and altered the landscape of histone H3 lysine 4 (H3K4) methylation genome wide. Cohorts of SAMD1-repressed genes are linked to erythropoietic activities. SAMD1 expression promoted extracellular signal-regulated kinase signaling via stem cell factor/Kit stimulation in progenitor populations. In erythroid precursor cells, SAMD1 cooccupies chromatin with LSD1 and GATA factors. Whereas SAMD1 downregulates levels of H3K4 dimethylation genome wide, contributing to gene repression, SAMD1 also elevates transcription at select sites. To test Samd1 function in hematopoiesis, we performed competitive transplant experiments in mice. Samd1-knockdown hematopoietic stem cells (HSCs) contributed more to peripheral blood mononuclear cells vs control HSCs. Our results establish SAMD1 as a coordinator of H3K4 methylation and stem/progenitor activity in hematopoiesis and erythropoiesis.